Performance of new apple rootstocks for Gala variety in Southern Brazil - Denardi,Frederico (2016)
Abstract The objective of this study was to evaluate the performance of Geneva(r) apple rootstocks for 'Gala'. The experiment was set in a complete randomized block design with four replications of tree plants per plot. It was used ten Geneva(r) rootstocks and M.9EMLA and M.7EMLA as controls. It was evaluated plant vigor, annual yield, cumulative yield, cumulative yield efficiency and fruit weight. For 'Gala' vigor control, G.10 and G.757 were more efficient than M.9EMLA; CG.2022 was equivalent and the other rootstocks were less efficient. 'G.24', 'G.969', 'G.30' and 'G.210' presented vigor equivalent to 'M.7EMLA'. 'G.896' was the most vigorous. Among dwarfing rootstocks, G.213 and G.757 were the most efficient on cumulative yield, the last showing the highest cumulative yield efficiency. Among semi-dwarfing, G.210 showed the highest cumulative yield and the highest cumulative yield efficiency. 'G.896' induced higher cumulative yield than 'M.7EMLA'. The greatest 'Gala' fruit weight was on 'G.213' and 'CG.2022'.